Approximate Prediction-Based Control Method for Nonlinear Oscillatory Systems with Applications to Chaotic Systems - Thiago P. Chagas; Pierre-Alexandre Bliman; Karl H. Kienitz (Journal of Control Science and Engineering)
The approximate Prediction-Based Control method (aPBC) is the continuous-time version of the well-known Prediction-Based Chaos Control method applied to stabilize periodic orbits of nonlinear dynamical systems. The method is based on estimating future states of the free system response of continuous-time systems using the solution from the Runge-Kutta implicit method in real time. Some aspects of aPBC are evaluated in the present work, particularly its robustness to low future states estimation precision is exemplified.